Development And Validation Of Hplc Method For Simultaneous Determination Of Haloperidol And Reduced Haloperidol In Plasma: Application In Pharmacokinetic Study - Asualingam, Theepa (2007)
Haloperidol merupakan suatu drug antipsikotik yang tipikal dan secara kimianya daripada kumpulan butirofenon.